ROLE OF PROBIOTICS, PREBIOTICS AND SYNBIOTICS IN ATOPIC DERMATITIS - Patricia Dian Putri (JURNAL WIDYA MEDIKA, 2022)
Atopic dermatitis (AD) is a chronic recurrent skin disease, causing itching, with a characteristic distribution of lesions. Giving a combination of probiotics for 8 weeks to children with atopic dermatitis resulted in relieving symptoms based on Scoring Atopic Dermatitis (SCORAD) index, decrease in IgE serum levels, interleukin (IL)-5, IL-6 and interferon γ compared to placebo group. While prebiotics have potential to promote the growth of various microflora in colon. Change in microflora are given an allergic protective effect by modulating postnatal immune development. Synbiotic approach the capacity synergy between probiotics and prebiotics. Synbiotic therapy is a promising therapy for AD